Erector spinae plane block: A narrative review with systematic analysis of the evidence pertaining to clinical indications and alternative truncal blocks - Saadawi, Mohammed; Layera, Sebastián; Aliste, Julián; Bravo, Daniela; Leurcharusmee, Prangmalee; Tran, De Q. (Journal of clinical anesthesia, 2021)
This narrative review discusses the anatomy, mechanism of action, techniques, pharmacology, indications, complications and substitutes for erector spinae plane (ESP) blocks. The Medline, Embase and Google Scholar databases (inception-last week of April 2020) were searched. For indications and alternative blocks, a systematic analysis of the available evidence was carried out. In order to highlight the best evidence available, only randomized trials with prospective registration, blinded assessment and sample size justification were retained for analysis. The collective body of anatomical studies suggests that ESP block may work through a combination of different mechanisms (e.g., local anesthetic spread to the thoracic paravertebral space, epidural space, and dorsal ramus). Compared to control, the available evidence suggests that ESP block results in decreased postoperative pain and opioid requirement for a wide array of thoracic and abdominal surgical interventions. Erector spinae plane blocks and thoracic paravertebral blocks seem to provide comparable benefits for thoracoscopic and breast cancer surgery when performed with a similar number of injections. Currently, ESP blocks should be favored over intercostal blocks since, at best, the latter provide similar analgesia to ESP blocks despite requiring multiple-level injections. In recent years, ESP blocks have become the topic of considerable clinical interest. Future trials are required to investigate their optimal technique, dose of local anesthetic and perineural adjuvants. Moreover, additional investigation should compare ESP blocks with robust multimodal analgesic regimens as well as truncal blocks such as thoracic epidural block, midpoint transverse process to pleura block, PECS block, quadratus lumborum block, and transversus abdominis plane block. •Erector spinae plane (ESP) blocks act through a combination of different mechanisms.•Compared to control, ESP blocks result in lower pain scores and opioid requirement for thoracic and abdominal surgery.•ESP and thoracic paravertebral blocks provide comparable benefits for thoracoscopic and breast cancer surgery.•Future trials should investigate the optimal technique, dose of local anesthetic and perineural adjuvant for ESP blocks.•Additional trials are required to compare ESP blocks to alternative blocks.